Developing Creative Competencies in Pencil Drawing through Modern Pedagogical Methods - Sa’diyev Soli Tolipovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article investigates the development of creative competencies in pencil drawing within higher pedagogical education. The study emphasizes the importance of modern pedagogical methods, including project-based learning, flipped classroom approaches, collaborative tasks, and the integration of digital technologies. It highlights how these strategies enhance students’ artistic skills, critical thinking, and professional readiness.